Suitability of Highly Polymerised Polyaluminium Chlorides (PACls) in the Treatment of Mixture of Groundwater and Surface Water - Izabela Krupińska (Molecules, 2023)
The aim of this study was to evaluate the effectiveness of the coagulation process using highly polymerised polyaluminium chlorides in reducing the level of pollution of water in a mixture of groundwater and surface water. The coagulants used were prehydrolysed polyaluminium chlorides with the trade names PAXHP908 and PAXXL1911 that had alkalinity 85% and different iron contents (<0.01% and 0.7%). The Al species distribution in the PACls (PAXXL1911 ad PAXHP908) samples were analysed by the Ferron complexation timed spectrophotometry. The content of polymer forms of aluminium (Alb) in the tested coagulants was 40%. The worse results in the removal of organic matter (TOC, DOC, UV254), iron, colour and turbidity in the coagulation process were produced by the PAXXL1911, possessing higher content of iron (0.7%). The lower usefulness of the PAXXL1911 was probably caused by the interaction of organic ligands present in the treated water and Fe(III) ions introduced into the water with the coagulant. The effectiveness of the coagulation process with the tested coagulants was also evaluated by measuring the electrokinetic potential ζ, which determines the stability of the colloidal system.